Main actors behind the endometrial receptivity and successful implantation. (December 2021) - Governini, Laura; Luongo, Francesca P.; Haxhiu, Alesandro; Piomboni, Paola; Luddi, Alice
Graphical abstract: Highlights: The establishment of pregnancy is dependent on successful implantation. The cross-talk between endometrium and embryo is a necessary condition for implantation. Endometrial receptivity during the implantation window requires a complex interaction by multiple agents. Identify the unknown obstacles of implantation and predict a positive pregnancy outcome. Abstract: Embryo implantation occurs during a short period of time, the implantation window, in the mid-secretory phase of the menstrual cycle. The cross-talk between the endometrium and the embryo, at the stage of blastocyst, is a necessary condition for successful implantation. Till now, no single molecule or receptor has been identified to play an essential role on embryo implantation but a huge number of mediators, including cytokines, lipids, adhesion molecules, growth factors, and others, are reported to support the establishment of pregnancy. Therefore, the aim of this review is not only to describe the different actors involved in the implantation process, but also to try to characterize the relationships between these factors as well as their time-regulated activation. Moreover, the availability of in vitro culture systems to study the interactions between embryo and endometrium as well as the paracrine communication regulated by exosomal vesicles will be investigated, as an innovative approach for a more precise characterization of the interactions between the different molecules involved in this process. The in-depth knowledge of all these complex mechanisms will allow to address the reasons of implantation failure and infertility, thus providing new avenues for promoting the successful establishment of a pregnancy.